2011
DOI: 10.1103/physrevb.83.241307
|View full text |Cite
|
Sign up to set email alerts
|

Spin-to-orbital angular momentum conversion in semiconductor microcavities

Abstract: We experimentally demonstrate a technique for the generation of optical beams carrying orbital angular momentum using a planar semiconductor microcavity. Despite being isotropic systems with no structural gyrotropy, semiconductor microcavities, because of the transverse-electric-transverse-magnetic polarization splitting that they feature, allow for the conversion of the circular polarization of an incoming laser beam into the orbital angular momentum of the transmitted light field. The process implies the for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 31 publications
(31 reference statements)
2
42
0
Order By: Relevance
“…4], [13, Figs. 2(c)-(d)] and [14], and that the underlying reason for their appearance is not SAM to OAM transfer, but that the electromagnetic duality symmetry is broken in those systems.…”
Section: Optical Vortices In Scatteringmentioning
confidence: 99%
See 3 more Smart Citations
“…4], [13, Figs. 2(c)-(d)] and [14], and that the underlying reason for their appearance is not SAM to OAM transfer, but that the electromagnetic duality symmetry is broken in those systems.…”
Section: Optical Vortices In Scatteringmentioning
confidence: 99%
“…The conversion between spin and orbital angular momentum is widely used to explain phase singularities in numerical simulations of tightly focused fields [9][10][11], and in scattering experiments: [12][13][14]. A detailed discussion of the SAM to OAM conversion can be found in [30].…”
Section: Exemplary Application Of the Framework: Revision Of Spin mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, much attention has been paid to a study of the possible generation of optical states possessing non-zero orbital angular momentum, which could find applications in quantum information processing. 12 Initially, microcavities were entirely realized with semiconductors, but recently it has been shown that the inclusion of metallic layers in a microcavity is interesting both for fundamental effects and applications: It was shown that the introduction of metallic components into a microcavity leads to the appearance of additional localized optical states, so called Tamm plasmons, 13 which can strongly couple to cavity polaritons. 14 In dielectric microcavities, metal layers can play numerous roles simultaneously: they lead to the appearance of Tamm plasmons and determine their eigenenergies and can be used to contact and control the properties of the device electrically.…”
mentioning
confidence: 99%